Kajian Posisi Destinasi Ekowisata Sungai Utik Berdasarkan Tourism Area Life Cycle - Senudin, Putriatre Krimasusini; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATA, 2023)
This study aims to analyze the condition of development in the Utik River ecotourism destination based on the Tourism Area Life Cycle (TALC) theory. This research is descriptive qualitative research, which is an approach to describe phenomena in the field through interview techniques, observation, and documentation regarding empowerment in Utik River Ecotourism. The data sources used are primary and secondary data. The technique of determining informants was carried out by the purpose sampling method. The results showed that the Utik River Ecotourism Destination had passed three stages of empowerment, namely the awareness stage which took place from 2011-2014, the capacity stage which was dominated by the role of NGOs (nongovernment organizations), the power giving stage which was dominated by the role of NGOs and the central government. Based on the TALC study, the utik river ecotourism destination is in the involvement stage. This stage is characterized by community initiatives in developing tourism through the provision of supporting facilities in the form of simple promotion. Keywords : Ecotourism, TALC, Empowerment